Phenotypic Analysis of Arrhythmogenic Cardiomyopathy in the Hutterite Population: Role of Electrocardiogram in Identifying High‐Risk Desmocollin‐2 Carriers. Issue 6 (11th December 2014) - Wong, Jorge A.; Duff, Henry J.; Yuen, Tiffany; Kolman, Louis; Exner, Derek V.; Weeks, Sarah G.; Gerull, Brenda
Abstract : Background: The p.Gln554X mutation in desmocollin‐2 (DSC2) is prevalent in ≈10% of the Hutterite population. While the homozygous mutation causes severe biventricular arrhythmogenic right ventricular cardiomyopathy, the phenotypic features and prognosis of heterozygotes remain incompletely understood. Methods and Results: Eleven homozygotes (mean age 32±8 years, 45% female), 28 heterozygotes (mean age 40±15 years, 50% female), and 22 mutation‐negatives (mean age 43±17 years, 41% female) were examined. Diagnostic testing was performed as per the arrhythmogenic right ventricular cardiomyopathy modified Task Force Criteria. Inverted T waves in the right precordial leads on ECG were seen in all homozygotes but not in their counterparts ( P <0.001). Homozygotes had higher median daily premature ventricular complex burden than did heterozygotes or mutation‐negatives (1407 [IQR 1080 to 2936] versus 2 [IQR 0 to 6] versus 6 [IQR 0 to 214], P =0.0002). Ventricular tachycardia was observed in 60% of homozygotes but in none of the remaining individuals ( P <0.001). On cardiac magnetic resonance imaging, homozygotes had significantly larger indexed end‐diastolic volumes (right ventricular: 122±24 versus 83±17 versus 83±12 mL/m 2, P <0.0001; left ventricular: 93±18 versus 76±13 versus 80±11 mL/m 2, P =0.0124) and lower ejection fraction values compared with heterozygotes and mutation‐negatives (right ventricular ejection fraction: 41±9% versus 59±9% versus 61±6%, P <0.0001; left ventricular ejection fraction: 53±8% versus 65±5% versus 64±5%, P <0.0001). Most affected individuals lacked right ventricular wall motion abnormalities. Thus, few met cardiac magnetic resonance imaging task force criteria. Conclusions: The ECG reliably identifies homozygous p.Gln554X carriers and may be useful as an initial step in the screening of high‐risk Hutterites. The cardiac phenotype of heterozygotes appears benign, but further prospective follow‐up of their arrhythmic risk is needed.